Research on Relay-Assisted Cellular System Coordination Mechanism Based on Energy-Efficient - Xue Jianbin; Zhao Yanqin; Qin Lijing; Liang Bo (Institute of Advanced Engineering and Science, 2013)
Multi-user and multi-business lead to dense deployment relay stations in the relay-assisted cellular system. When active relay stations exceed actual needs, decreasing the network energy efficiency has direct correlation with web users, business, distribution and other parameters. In the case that satisfying requirements of service quality, such as delay and rate are satisfied, this paper mainly research on how to dynamically adjust the activation time and the number of relay stations according to the location of relay stations in the networks. In the meantime, we research on improving the efficiency of system energy and resource matching through the data forwarding of relay stations which have been activated. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2925